STATUS GIZI WANITA USIA REPRODUKTIF TERHADAP PENYAKIT DIABETES MELITUS TIPE 2 - Zulfitriani Murfat; Rasfayanah Rasfayanah; Rachmat Faisal Syamsu; Asrini Safitri; Nur Ashianty Hadijah (Universitas Pahlawan, 2022)
Nutritional status is the main parameter that is widely used in monitoring the suitability of daily nutritional intake with nutritional needs. Assessment of nutritional status is one way of measuring to detect a balance disorder between nutrients and daily needs that can trigger health problems, namely diabetes mellitus. This study uses the Literature Review method by referring to national and international articles that are relevant to the research study. There are 17 articles obtained through the Pubmed database, Clinical Key, Google Scholar and Openknowledgemaps from 2017 to 2021. Based on the analysis results of this research study, it can be concluded that women are more at risk of having a tendency to suffer from diabetes mellitus because physically there is an increase in nutritional status which is influenced by hormones. during preconception, pregnancy and menopause. Lifestyle changes are an effort to reduce risk factors for diabetes mellitus